AN ANALYSIS OF PERLOCUTIONARY ACTS ON THE ELEVENTH GRADE ENGLISH TEACHER’S TALK OF SMA N 4 MAGELANG IN THE SCHOOL YEAR 2015/2016 - Erest Mandarevina; Dwi Winarsih; C. Prima Ferri Karma (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2018)
Communication is a way to deliver information to the hearer. In teaching and learning process, communication has an essential role. The success of communication depends on the participants involve. In this circumstance the participants are teacher and students. Teacher‟s talk has a major influence to the students. The utterance that is produced by the teacher is very influential on students‟ understanding when the teacher delivers the material to the learners. What the teacher utters affects the students.  The objectives of this research are to analyze the effects of perlocutionary acts and to find the dominant effects of perlocutionary acts that are found in teacher‟s talk by English teacher in delivering material. The subject of this research is English teacher‟s talk of SMA Negeri 4 Magelang, focus on sentence that is produced by the teacher. In conducted the research the writer recorded the teacher‟s talk during teaching and learning process. Furthermore, the writer transcribed the data and analyzed the data to find the effects of perlocutionary acts found in teacher‟s talk. Based on the result analysis, the writer found that there are 11 effects of perlocutionary acts used by the teacher. The writer concluded that the dominant effects of perlocutionary acts are hearer thinks of something, hearer does something and hearer gives answer. Those three effects are related each other. It shows the pattern of communication in teaching and learning process.